KOMPARASI STRATEGI INVESTASI AKTIF DAN PASIF UNTUK OPTIMALKAN RETURN SAHAM YANG TERDAFTAR DI BURSA EFEK INDNESIA - Kusumawardana, Venus (Journal of Innovation in Business and Economics, 2016)
The purpose of this study was to test an active strategy (moving leverage) with a passive strategy (buy, sell and hold strategy) to determine which strategy to generate optimal returns with to compair of all strategy. Method by collecting data is then processed and analyzed using software ChartNexus. An indicators moving everage 5, 10, 30, bollingerband and compare the return of an active strategy with passive strategies. The results of this research note that suitable and appropriate technical analysis to forecast stock prices to determine buy, sell and hold, to optimize stock returns and shows that an active strategy is able to out perform a passive strategy when the market is bearish and volatile. The use of passive strategies can provide superior results, when used on a very bullish market conditions. Volatile market conditions that are more suitable to use the strategy of comparison between the strategies of active and passive strategies.